Immunohistochemical Expression of BRCA1 and BRCA2 in a Cohort of Ugandan Men with Prostate Cancer: an analytical cross-sectional study - Amsi, Patrick T.; Yahaya, James J.; Kalungi, Sam; Odida, Michael (African Journal of Urology, 2020)
Mutation of the tumour suppressor genes BRCA1 and BRCA2 is thought to cause early development of prostate cancer which has poor prognosis. The purpose of this study was to determine the expression of BRCA1/2 and correlate it with clinicopathological factors for patients with prostate cancer in Uganda. Retrospectively, we used immunohistochemistry to evaluate the expression of BRCA1/2 antibodies in tissue blocks of 188 patients with prostate cancer who were diagnosed between January 2005 and December 2014 in the Department of Pathology, Makerere College of Health Sciences. The Chi-Square test was used to determine the association of the categorical variables, whereas t-test was used to compare groups of mean of the variables in the study. Expression of BRCA1 and BRCA2 was found in 26.1% and 22.9% cases, respectively. Co-expression of BRCA1 and BRCA2 was found in only 7.4%. Gleason score was associated with expression of BRCA1 and BRCA2 (P = 0.013, P = 0.041, respectively). Age was not associated with BRCA1 and BRCA2 expression; P = 0.543, P = 0.091, respectively. Likewise, PSA was not associated with BRCA1 and BRCA2 expression; P = 0.446, P = 0.399, respectively. BRCA1 and BRCA2 proteins in this study were expressed more in cases with poorly differentiated prostate cancer than in cases with either well or moderately differentiated prostate cancer. Co-expression of BRCA1 and BRCA2 proteins in the same patient in our study was 3 times less than either BRCA1 or BRCA2 alone.
Keywords: Prostate cancer; BRCA1; BRCA2; Immunohistochemistry